2008
DOI: 10.1021/bm800291v
|View full text |Cite
|
Sign up to set email alerts
|

Addition of “Charge-Shifting” Side Chains to Linear Poly(ethyleneimine) Enhances Cell Transfection Efficiency

Abstract: We reported recently that the addition of ester-functionalized, "charge-shifting" side chains to linear poly(ethyleneimine) (LPEI) can be used to design polyamines that promote both self-assembly and self-disassembly with DNA in aqueous environments. This investigation sought to characterize the influence of charge-shifting side chains on the ability of LPEI to mediate cell transfection and understand the extent to which increases (or decreases) in levels of transfection could be understood in terms of time-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…to make the polymers less positively charged [106,107] or negatively charged (charge reversal) [108] upon hydrolysis of ester groups into negatively charged groups to facilitate gene unpacking. The advantage of pCB-ester polymers is that they will be hydrolyzed into zwitterionic polymers, which have been shown to be ultralow fouling and biocompatible.…”
Section: Dna/pcb Ester Complexesmentioning
confidence: 99%
“…to make the polymers less positively charged [106,107] or negatively charged (charge reversal) [108] upon hydrolysis of ester groups into negatively charged groups to facilitate gene unpacking. The advantage of pCB-ester polymers is that they will be hydrolyzed into zwitterionic polymers, which have been shown to be ultralow fouling and biocompatible.…”
Section: Dna/pcb Ester Complexesmentioning
confidence: 99%
“…Intelligent polymers that can alter their interactions with therapeutic genes by sensing changes in pH [14], redox potential [15], temperature [16], UV irradiation [17], and enzyme activity [18][19][20][21][22][23][24][25], have been promoted as gene carriers. We have extensively studied polymer-peptide conjugates that release pDNA in response to protein kinases (PKs) [18][19][20][21][22][23][24] and proteases [25], both specifically and abnormally activated in diseased cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others have demonstrated that it is possible to design ‘charge-shifting’ polymers, and exert control over the rates and extents of changes in charge state, by incorporating hydrolyzable side chains into the structures of cationic or anionic polymers [3847]. Several different approaches to the design of cationic ‘charge-shifing’ polymers have been reported, largely in the context of developing new materials for the polyplex-mediated delivery of DNA (e.g., to provide control over the disassembly of cationic polymer/DNA complexes in solution or in cells) [4147]. …”
Section: Introductionmentioning
confidence: 99%